2009
DOI: 10.1038/nmat2419
|View full text |Cite
|
Sign up to set email alerts
|

A cell-free protein-producing gel

Abstract: Proteins are important biomaterials and are generally produced in living cells. Here, we show a novel DNA hydrogel that is capable of producing functional proteins without any living cells. This protein-producing gel (termed 'the P-gel system' or 'P-gel') consists of genes as part of the gel scaffolding. This is the first time that a hydrogel has been used to produce proteins. The efficiency was about 300 times higher than current, solution-based systems. In terms of volumetric yield, the P-gel produced up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
275
0
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 302 publications
(293 citation statements)
references
References 32 publications
6
275
0
12
Order By: Relevance
“…The potential of applying this hydrogel for drug delivery application has also been demonstrated. Very recently, this group also reported that by incorporating linear plasmids into polymer network, this hydrogel is capable of generating natural proteins under cell-free conditions (Park et al 2009). By using the similar Y-shaped DNA building blocks, but a different mechanism to connect these building blocks, Cheng group also put forth a hydrogel design based entirely on DNA nanostructures (Cheng et al 2009).…”
Section: Dna-only Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of applying this hydrogel for drug delivery application has also been demonstrated. Very recently, this group also reported that by incorporating linear plasmids into polymer network, this hydrogel is capable of generating natural proteins under cell-free conditions (Park et al 2009). By using the similar Y-shaped DNA building blocks, but a different mechanism to connect these building blocks, Cheng group also put forth a hydrogel design based entirely on DNA nanostructures (Cheng et al 2009).…”
Section: Dna-only Networkmentioning
confidence: 99%
“…Additionally, DNA gels have been shown to be an ideal candidate for cell capsulation (Um et al 2006b), potentially, serving as in vivo protein factory for protein synthesis and delivery (Park et al 2009). Examples of the studies using DNA-only, DNA-as-backbone, and DNA crosslinked macromaterials on potential drug or gene delivery applications and the kinetics of release are in Figure 7.…”
Section: Drug Delivery Vehiclementioning
confidence: 99%
“…Later, the immobilization of biomolecule and synthetic solid-phase approaches have been successfully aided research for a widespread applications for both pre-translated biomolecules such as RNA/DNA and post-translated biomolecules such as protein/enzymes including SNP genotyping [16], DNA amplification [17], differential display [18], in vitro transcription [19], immunoassay [20,21], and others while promoted the development of microfabrication [22,23], high-throughput screening and automation strategies in many areas including proteomics. Very recently, a hydrogel-based system was introduced that improved the efficiency of CFPS up to 300 times than solution phase-based system [24].…”
Section: Solid-phase Versus Solution-phase Chemistry For Protein Syntmentioning
confidence: 99%
“…Dendrimer-like DNAs such as X-shaped DNA (X-DNA) and Y-shaped DNA (Y-DNA) have attracted great interest for using DNAs as a generic instead of a genetic material. 24,25 These DNA building blocks can be readily incorporated into larger structures in a controlled manner and the controlled assembly is robust and efficient yielding stable and almost monodisperse entities. Herein, we report X-DNA and Y-DNA templated syntheses of Ag NCs and their optical properties.…”
mentioning
confidence: 99%